Genome-wide identification and characterization of the bZIP family in the Mangrove Plant Kandelia obovata and its role in response to stress - Yuchong Yi; Yuting Qiu; Hongyao Hu; Dandan Qin; Hechen Huang; Taiping Chen; Wenqi Zha; Yingjia Shen (BMC Plant Biology)
Abstract Background The basic leucine zipper (bZIP) transcription factors play crucial roles in plant growth, development, and responses to environmental changes. The mangrove plant Kandelia obovata, native to subtropical and tropical coastal intertidal zones, has evolved various adaptive mechanisms to cope with unstable muddy substrates, tidal fluctuations, saltwater intrusion, and intense ultraviolet radiation. This study aims to provide a comprehensive characterization of the bZIP gene family in K. obovata and investigate its functional roles in response to environmental stresses. Results In the K. obovata genome, 66 bZIP genes were identified and named KobZIP1 to KobZIP66, categorized based on their chromosomal locations. These KobZIP genes exhibited diversity in physicochemical properties, such as protein length, molecular weight, and isoelectric point, and were all predicted to localize to the nucleus. Phylogenetic and structural analyses classified the KobZIP genes into 12 subfamilies, with subfamily A containing the majority of members. Gene structure analysis revealed variations in the number and position of exons and introns among subfamilies, reflecting their evolutionary history and potential functional diversity. Conserved motif analysis showed that all bZIP family members contained motifs in the basic and hinge regions, with subfamily D displaying the greatest motif diversity. Promoter region analysis identified various cis-acting elements associated with responses to phytohormones (ABA, GA, ET, IAA, MeJA, SA) and environmental stress. The expression patterns of KobZIP genes across different tissues and under various abiotic stress conditions were analyzed using transcriptomic data and experimental validation. Conclusion This study provides a comprehensive characterization and functional analysis of the bZIP gene family in K. obovata, offering new insights into their roles in plant development and environmental adaptation. The expression profiles of KobZIP genes during root development and post-embryonic stages, along with their responses to ABA, low temperature, and salt stress, underscore their potential significance in the adaptation of mangrove plants to the intertidal environment.